2015
DOI: 10.1007/978-3-319-14406-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fluorescent Nanofibers for Explosive Detection

Abstract: Development of an instant on-site visual detection method for 2,4,6 trinitrotoluene (TNT) has become a significant requirement of the hour towards a secured society and a greener environment. Despite momentous advances in the respective field, a portable and reliable method for quick and selective detection of TNT still poses a challenge to many reasons attributing to inappropriate usage in subordinate areas and untrained personnel. The recent effort on the fluorescent based detection represents as one of easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…As a result of their sub‐micron dimensions, nanofibers possess unique properties including a high volume of small pores and a good inter‐pore connectivity, resulting in a remarkably high specific surface area . These properties are interesting for many application areas and particularly sensors, as a large specific surface area results in fast response times and ultra‐sensitivity . Compared to bulk materials, films and coatings, nanofibers are reported to enhance the sensitivity and responsivity of sensors .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of their sub‐micron dimensions, nanofibers possess unique properties including a high volume of small pores and a good inter‐pore connectivity, resulting in a remarkably high specific surface area . These properties are interesting for many application areas and particularly sensors, as a large specific surface area results in fast response times and ultra‐sensitivity . Compared to bulk materials, films and coatings, nanofibers are reported to enhance the sensitivity and responsivity of sensors .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hahn et al fabricated a sensor based on polyacrylonitrile nanofibers loaded with metal oxide semiconductors (Fe 2 O 3 , Ab‐SnO 2 , and ZnO) to detect CO 2 , which was visualized and quantified by FTIR spectroscopy . Optical nanofibrous sensors based on fluorescence involve quenching/regaining the fluorescence of the detection system due to the interaction with the analyte . This phenomenon is generally measured by Stern–Volmer plots and visualized by fluorescent microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated electrospun nanofibers as an excellent matrix for protecting and enhancing the sensing performance of fluorescent gold nanoclusters and metallic nanoparticles [22][23][24][25][26]. The polysulfone fiber-based membranes received much attention in the field ranging from artificial kidneys for blood purification to water treatment and food processing, owing to their good permeability, mechanical, thermal, and biocompatible properties [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a need for considerable effort towards the development of sensitive and selective sensor for on-site visual detection is the want of the hour. In recent years, major study has gone into the analysis of fluorescence based sensors owing to their high sensitivity, ease of operation, time-efficiency and sensitivity characteristics 4 5 6 7 8 . Moreover, significant progress has also been made to develop a variety of fluorescent probes and subsequent color changes with their aggregation in the presence of analytes has been investigated and studied in the recent past 9 10 11 .…”
mentioning
confidence: 99%